Dermatology clinical case - Costa Azevedo, André (2021)
Herein are reported two cases of a previously healthy fourteen-year-old girl and a nine-year-old boy who presented to the Pediatric Emergency Department with a cutaneous reaction after applying a temporary black henna tattoo. Diagnosis of delayed hypersensitivity to black henna was established. Black henna tattoos are known for their temporary and harmless nature, but henna usually contains paraphenylendamine (PPD), originating black henna. PPD induces skin sensitization and causes allergic contact dermatitis.